Clinical and epidemiological characteristics of 1420 European patients with mild‐to‐moderate coronavirus disease 2019. (17th June 2020) - Lechien, Jerome R.; Chiesa‐Estomba, Carlos M.; Place, Sammy; Van Laethem, Yves; Cabaraux, Pierre; Mat, Quentin; Huet, Kathy; Plzak, Jan; Horoi, Mihaela; Hans, Stéphane; Rosaria Barillari, Maria; Cammaroto, Giovanni; et al.
Abstract: Background: The clinical presentation of European patients with mild‐to‐moderate COVID‐19 infection is still unknown. Objective: To study the clinical presentation of COVID‐19 in Europe. Methods: Patients with positive diagnosis of COVID‐19 were recruited from 18 European hospitals. Epidemiological and clinical data were obtained through a standardized questionnaire. Bayesian analysis was used for analysing the relationship between outcomes. Results: A total of 1, 420 patients completed the study (962 females, 30.7% of healthcare workers). The mean age of patients was 39.17 ± 12.09 years. The most common symptoms were headache (70.3%), loss of smell (70.2%), nasal obstruction (67.8%), cough (63.2%), asthenia (63.3%), myalgia (62.5%), rhinorrhea (60.1%), gustatory dysfunction (54.2%) and sore throat (52.9%). Fever was reported by 45.4%. The mean duration of COVID‐19 symptoms of mild‐to‐moderate cured patients was 11.5 ± 5.7 days. The prevalence of symptoms significantly varied according to age and sex. Young patients more frequently had ear, nose and throat complaints, whereas elderly individuals often presented fever, fatigue and loss of appetite. Loss of smell, headache, nasal obstruction and fatigue were more prevalent in female patients. The loss of smell was a key symptom of mild‐to‐moderate COVID‐19 patients and was not associated with nasal obstruction and rhinorrhea. Loss of smell persisted at least 7 days after the disease in 37.5% of cured patients. Conclusion: The clinical presentation of mild‐to‐moderate COVID‐19 substantially varies according to the age and the sex characteristics of patients. Olfactory dysfunction seems to be an important underestimated symptom of mild‐to‐moderate COVID‐19 that needs to be recognized as such by the WHO. Abstract :